On FS+-Domains - Yayan Yuan; Jibo Li (Abstract and Applied Analysis)
We introduce a new construction—FS+-domain—and prove that the category with FS+-domains as objects and Scott continuous functions as morphisms is a Cartesian closed category. We obtain that the Plotkin powerdomain PP(L) over an FS-domain L is an FS+-domain.